PERCERAIAN DI LUAR PENGADILAN MENURUT TINJAUAN HUKUM ISLAM: (Studi Kasus Di Desa Lariang Kecamatan Tikke Raya Kabupaten Pasangkayu Provinsi Sulawesi Barat) - Nurfaradillah AS; Muh. Syarif Hasyim; Sitti Nurkhaerah (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2020)
The discussion in this research is divorce outside the court according to the study of Islamic law in Desa Lariang Kecamatan Tikke Raya Kabupaten Pasangkayu. The basis for this research is that divorce outside the court is contrary to the laws enacted in Indonesia, namely: Law of the Republic of Indonesia Number 1 of 1974 concerning Marriage and Presidential Instruction Number 1 of 1991 concerning Compilation of Islamic Law.So that the research will use a qualitative research approach, with the research design used is a single case study design in research. According to a review of Islamic law, divorce that occurs outside the court in Lariang Village is legal. However, when viewed in Law Number 1 of 1974 concerning Marriage and Presidential Instruction Number 1 of 1991 concerning Compilation of Islamic Law (positive Islamic law) this is invalid.